Introduction to Special Issue Expanding Landscapes of Academic Writing in Academia - Vera E. Woloshyn; Sam Illingworth; Snežana Obradović-Ratković (Brock Education: a Journal of Educational Research and Practice, 2024)
Academic writing is essential for disciplinary learning, academic success, knowledge creation, social status, and career advancement within academia (Fang, 2021). Academic research, writing, and publishing form the foundations of the majority of academic positions and remain primary considerations for hiring, renewal, promotion, and tenure in most higher education institutions (Ratković et al., 2019; Rawat & Meena, 2014). Early-career researchers must establish a significant track record of research, including publishing in high-impact journals (Couch, 2020). In graduate programs, academic writing competencies are critical for student success, with doctoral students often led to believe that they must be prolific academic writers to gain entry and advancement within academia (Mandke, 2019).